PERANCANGAN JADWAL PRODUKSI DENGAN MENGGUNAKAN METODE HEIJUNKA UNTUK MENDUKUNG PENGEMBANGAN SISTEM PRODUKSI KONVENSIONAL KE SISTEM PRODUKSI TOYOTA (STUDI KASUS: PT ADYAWINSA DINAMIKA) - Amran, Tiena G.; Imdam, Irma Agustiningsih (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
Customers nowadays demand high quality, affordable cost and fast and accurate delivery, which has pressurised the industry to make adjustment in order to meet customer needs. PT Adyawinsa Dynamics as one of the manufacturing industry engaged in the manufacture of dies, molding, and stamping, also strives to improve in meeting customer demands by referring to the Toyota Production System. Improvements can be done in the companys production system by planning a production plan based on the heijunka concept which is the foundation / basis of the implementation of the Toyota Production System. Problems occuring in the production line are consumer demand that always change, and unavailability of appropriate production control tools to cope with fluctuations in demand for parts and good control of production planning. Results of analysis shows decrease in stock since production will be run if there is demand from customers, and responding to customer needs can be quickly met.